The Relationship Between Mater Matuta and Aurora - Janovics, Anna (Sapiens ubique civis, 2023)
The Matralia, an event attended only by women to worship Mater Matuta or Mother Matuta, was annually held in Italy on 11th of June. The celebration was bound to start in the morning at the first sight of prima lux—probably this is why Mother Matuta is often identified with several goddesses whose origins and mythology are tied to the celestial sphere. One of these figures known to the Romans was Aurora, the goddess of dawn. In various scriptures, these two female figures are mentioned together with their identities intertwined. This paper aims to further explore these points of connection.